Gambaran Partisipasi Masyarakat terhadap Pengendalian Vektor Melalui Kajian Tempat Perkembangbiakan Aedes aegypti di Kota Bandung - Lia Faridah; Titik Respati; Sunarjati Sudigdoadi; Hadyana Sukandar (Majalah Kedokteran Bandung, 2017)
In 2014, Bandung has the highest number of Dengue Fever cases of 27 districts and cities in West Java. Dengue Fever control efforts have been implemented for several decades. One of the efforts is the eradication of the vector breeding site with community participation. The aim of this study was to assess community participation by identifying Aedes aegypti’s breeding sites, both indoor and outdoor, in Bandung area. Sampling was conducted on houses in 16 villages throughout Bandung area. The sampling points were selected according to the Dengue Fever event number, population density, height, and socio-economic status. The total sample points were 1983 houses. Larvae from sample points were collected from various water containments, both natural and manmade, around the settlement. The larvae samples were then brought to the laboratory to be identified and counted. Results indicated the dominant breeding sites were bathtub (50%), gutter (24%), and dispenser (15%). Entomological survey resulted in 24% HI, 12% CI, and 36% BI. This indicates the lack of community participation in preventing DF by eradicating vector’s breeding sites and Bandung is still potential for DF outbreak.